ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM PENGGUNAAN APLIKASI GRAB (STUDI KASUS : MAHASISWA STMIK NUSA MANDIRI JAKARTA) - Irfan Mahendra; Nelly Septiany (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2018)
The quality of mobile applications has a very important role to build a competitive advantage of the company, so the company should be concerned to maintain the quality of applications, to always with users needs and wants. One way that can be taken is to evaluate the mobile application used. So based on evaluation results, it can be known improvement steps. The purpose of this research is to analyze the factors that influence students intention in STMIK Nusa Mandiri Jakarta in use Grab Application using Modified Technology Acceptance Model. This research was conducted with the case study method to students of STMIK Nusa Mandiri Jakarta that uses Grab Application. The sample in this research is 60 respondents, determined using non-probability sampling approach, with incidental sampling technique. The results of this research are independent variables simultaneously significant effect on behavior intention using Grab Application. While partially, perceived usefulness variable, perceived ease of use, attitude technology use, and self-efficacy variable significant effect on behavioral intention using Grab Application. Whereas subjective norm variables did not significantly affect the behavior of the variable behavioral intention using the Grab Application.